BARREIRAS VEGETAIS VERDES COMO ATENUADORAS DO RUÍDO AMBIENTAL: ESTUDO DE CASO EM IRATI-PR - SPLIETHOFF, JHENIFER (2022)
The present study aims to evaluate the potential of the Secondary Mixed Ombrophilous Forest as a vertical noise-attenuating green barrier. The methodology foresees the elaboration of an analysis of proximity between sampling points of omnidirectional monitoring of the noise to be measured at different distances of proximity to the source from the beginning of the barrier and inside the forest. A sound source reproducing amplified pink noise was used. In this research, it was An experimental strategy was used to prove the influence of this type of green plant barrier as a noise attenuator as one enters the interior of a fragment of Mixed Ombrophilous Forest, carrying out successive measurements of the sound pressure level at distances from the proximity of the source and the distances from the edge towards the interior of the forest that can prove the significant attenuating function of this type of green vertical barrier. In fact, the analyzes performed for LZeq A e Z (dB) confirm a significant correlation for distance from the source regardless of the sound amplitude for measurements performed outside the barrier (in front of the source, 6 m behind the source, 6 meters in front of the source) noise attenuation occurs as the sound propagates. However, the analyzes inside the barrier (12m, 18m and 24m) present a negative correlation for distance, confirming the hypothesis of effectiveness of the attenuation by the vegetal barrier.